Synthesis and reactivity studies of Group 5 imido and hydrazido complexes - Gamero-Vega, K (2018)
This Thesis describes the synthesis and reactivity of Group 5 imido and hydrazido complexes with tridentate, trianionic ligands. Various synthetic routes towards these hydrazido compounds were explored and in which several intermediates were synthesised and their chemistry was explored. The reactivity of the imido and hydrazido complexes with unsaturated and other small molecules was also studied. Chapter One provides a general introduction to tridentate pincer and tripodal ligands. The structure, synthesis and reactivity of Group 4 and 5 imido and hydrazido complexes is also reviewed. Chapter Two describes three different synthetic routes towards tantalum hydrazido complexes with tridentate, trianionic ligands. Synthesis, characterization and bonding analysis of the precursor dichloride species Ta(NN2SiMe3)Cl2, which is used as starting material for two of the synthetic routes, is also described. The synthesis, characterization and bonding analysis of the tantalum dialkyl and alkyl-amido precursors prepared in the multistep route is also explored. Chapter Three describes the synthesis and characterisation of Group 5 imido complexes with tridentate, trianionic ligands of the type Li3(NN2R) and Li3(NNNSiMe3). Reactivity studies of the imido complex Nb(NN2iPr)(NtBu)(py)2 with unsaturated and other small molecules are also explored. Chapter Four describes the synthesis and characterisation of Group 5 hydrazido complexes with tridentate, trianionic ligands by two different synthetic routes, alongside a bonding analysis of the imido compounds M(NN2R)(NtBu)(py)2 and their hydrazido analogues M(NN2R)(NNPh2)(L)x. Reactivity studies of the hydrazido complex Nb(NN2iPr)(NNPh2)(py)2 with unsaturated and other small substrates are also described. Chapter Five presents full experimental procedures and characterising data for the new methodologies and complexes reported in this Thesis.